Oxford readings in Indian art - Goswamy, B. N.; Agrawal, Vrinda (Oxford University press, 2018)
The world of art is complex and challenging in general; in India it is even more so because the documentation here is truly thin, and whatever exists is so widely scattered that it becomes a task in itself to locate it. This book address both these issues and brings together in one volume a remarkable body of material consisting not of speculations or theories but of original, primary sources. The voices one 'hears' in these excerpts are true and authentic, and if there are any speculations or interpretations, they come from texts or persons directly involved in the making or the understanding of the art of India. Sages speak here, in these pages, of the inter-relationships between the arts, practitioners record measurements of units of time and space, iconographers lay down rules and practices, artists record their experiences and patrons their delights. Information gathered from colophons is documented; excerpts are taken from memoirs and contemporary histories; the work of early writers on the arts is presented. Slowly, as one dips into these sources, one can hear the past speak, and the arts of India that have been lost to history come alive.